Transformasi Manajemen Sumber Daya Manusia: Strategi Inovatif Meningkatkan Produktivitas Ekonomi dalam Organisasi Publik dan Bisnis di Era Digital - Naya Syaqila Aqla (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
The development of digital technology has significantly changed the way organizations manage human resources (HR), both in the public and business sectors. Organizations are now required to transform from an administrative HR management system to a technology-based strategic role to improve efficiency, competitiveness, and economic productivity. The results show that HR management transformation plays a significant role in improving organizational performance through the implementation of digital technologies such as Human Resource Information Systems (HRIS), people analytics, big data, and artificial intelligence (AI). This transformation can improve work efficiency, accelerate decision-making processes, and encourage innovation and collaboration. In the public sector, human resource digitalization supports bureaucratic reform towards transparent and accountable governance, while in the business sector, it strengthens employee competitiveness and creativity. However, key challenges identified include the digital competency gap, resistance to change, and limited technological infrastructure, particularly in public organizations and developing regions. The study concluded that the success of human resource transformation depends not only on technology adoption but also on organizational cultural readiness, visionary leadership, and the continuous development of digital competencies. Synergy between people and technology is key to achieving sustainable economic productivity in the digital era.